Analytical study of geometric motifs in Zahak dreaming picture in Tahmasebi Shahnameh - Sahar Zekavat; Khashayar Ghazizadeh (پیکره, 2021)
Problem definition: Tahmasebi Shahnameh is an exquisite manuscript of Ferdowsi Shahnameh which belongs to the tenth century AD. This edition contains 258 paintings of the legends, myths, epic poems and stories of Shahnameh in 1200 pages, illustrated by the most prominent painters and calligraphers of the Safavid era. The paintings of Tahmasebi Shahnameh are of great artistic value and many decorative motifs have been employed in them. The geometric decorative motifs are considered as the most prominent and common ones in these paintings. The painting of Zahak dream is one of the drawings of this Shahnameh in which many decorative geometric motifs can be observed in various and beautiful compositions. The important place of geometric decorative motifs in Islamic art decorations, especially painting, has been the main concentration of the present research. It has been attempted to answer the question that what is the maximum number of repetitions of geometric motifs in this drawing? Objective: The present study aims to quantitatively and qualitatively identify the decorative and geometric patterns of Zahak dream painting as an important Iranian visual documents. Research method: The required information has been collected from library sources and historical documents and have been presented with a qualitative approach and in a descriptive-analytical manner. Resulte: The present results indicated that a number of 26 geometric compositions are present in Zahak dream painting of Tahmasebi Shahnameh. These compositions are composed of 19 types of geometric patterns, among which, the geometric patterns, regular hexagons and sun sixes met the highest amount of repetition in the studied drawing, respectively.